1987
DOI: 10.1210/endo-121-1-14
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Stimulatory Noradrenergic and Inhibitory Dopaminergic Regulation of Oxytocin Release in the Lactating Rat*

Abstract: The present experiments tested the involvement of central catecholaminergic systems in the suckling-induced release of oxytocin (OT) during lactation in the rat. In the first experiment, female rats in midlactation were separated from their offspring for 4 h and then allowed to suckle their litters for 30 or 60 min or to remain nonsuckled. The turnover rates of norepinephrine (NE) and dopamine (DA) were calculated from the rate of decline after synthesis inhibition. Suckling decreased the turnover rate of DA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
49
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 33 publications
7
49
1
Order By: Relevance
“…During parturition, the norepinephrine concentration in the SON rises prior to and in parallel with increases in blood levels of oxytocin (Herbison et al, 1997). Blockade of noradrenergic inputs to the hypothalamus with 6-hydroxydopamine lesion or with ␣ 1 -adrenoreceptor antagonists inhibits the reflex release of oxytocin associated with milk ejection (Tribollet et al, 1978;Clarke et al, 1979;Crowley et al, 1987). Similarly, reflex vasopressin release in response to unloading of arterial baroreceptors is accompanied by a rise in the concentration of norepinephrine in the PVN (Van Huysse and Bealer, 1991), which is caused by the activation of A1 noradrenergic projections .…”
Section: Abstract: Hypothalamus; Paraventricular Nucleus; Oxytocin; mentioning
confidence: 99%
“…During parturition, the norepinephrine concentration in the SON rises prior to and in parallel with increases in blood levels of oxytocin (Herbison et al, 1997). Blockade of noradrenergic inputs to the hypothalamus with 6-hydroxydopamine lesion or with ␣ 1 -adrenoreceptor antagonists inhibits the reflex release of oxytocin associated with milk ejection (Tribollet et al, 1978;Clarke et al, 1979;Crowley et al, 1987). Similarly, reflex vasopressin release in response to unloading of arterial baroreceptors is accompanied by a rise in the concentration of norepinephrine in the PVN (Van Huysse and Bealer, 1991), which is caused by the activation of A1 noradrenergic projections .…”
Section: Abstract: Hypothalamus; Paraventricular Nucleus; Oxytocin; mentioning
confidence: 99%
“…In vivo experiments have shown that intracerebroventricular (Bridges et al 1976;Moos and Richard 1982) or direct injection of DA into the SON (Urano and Kobayashi 1978) could induce or facilitate the release of neurohypophysial hormones. In lactating rats, OT release is facilitated or inhibited through the activation of D1 or D2 receptors, respectively (Crowley et al 1987;Parker and Crowley 1992). In vitro, dopamine has been reported to depolarize SON neurons directly through the activation of D2-like receptors (Yang et al 1991), whereas activation of presynaptic D4 receptors has been found recently to inhibit glutamatergic transmission (Price and Pittman 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, adrenergic afferents from the nucleus of the solitary tract to magnocellular nuclei (30) are activated by signals from the uterus via spinal pathways, causing OT release during labor and delivery (2,12,25). Central NE is increased during parturition (16) and suckling (3, 9), and stimulation of ␣-adrenergic receptors increases systemic and intranuclear OT release during lactation in suckled and nonsuckled rats (3,9,29,38).Histamine (HA) has also been shown to be important in the central control of OT during parturition and lactation. Histaminergic neurons make synaptic contact with OT neurons (40), and central administration of HA increases systemic OT release (4, 19), OT mRNA levels (20), and c-fos expression in OT containing neurons (21).…”
mentioning
confidence: 99%
“…Notably, adrenergic afferents from the nucleus of the solitary tract to magnocellular nuclei (30) are activated by signals from the uterus via spinal pathways, causing OT release during labor and delivery (2,12,25). Central NE is increased during parturition (16) and suckling (3,9), and stimulation of ␣-adrenergic receptors increases systemic and intranuclear OT release during lactation in suckled and nonsuckled rats (3,9,29,38).…”
mentioning
confidence: 99%